Decrease Treatment Burden following the Application of ADCES7 and WHOICOPE in a Diabetic Frail Elderly Lady with Multimorbidity - Chiu, Tsai-tung; Hsu, Hui-Chun; Lee, Yau- Jiunn; Hwu, Der-Wei (Archives of Clinical and Medical Case Reports, 2023)
Abstract not available in the source database.